PTH-247 Modern pelvic chemoradiotherapy techniques continue to cause bile acid malabsorption. (22nd June 2015) - White, KL; Henson, CC; Jenner, K; Burden, S; Lal, S; Davidson, SE; McLaughlin, J
Abstract : Introduction: During treatment with pelvic radiotherapy 80% of patients will develop diarrhoea. Patients with worse acute toxicity are at risk of developing more severe late bowel effects. It has previously been found that 44–57% of patients develop bile acid malabsorption (BAM) during pelvic radiotherapy. In the context of newer radiotherapy techniques, when there should be less small bowel exposure, we aimed to determine whether BAM remains a significant problem in this cohort of patients. Method: This study was part of a trial evaluating the role of a gastrointestinal intervention for patients with cervical and bladder cancer receiving chemoradiotherapy. When patients developed lower gastrointestinal symptoms a SeHCAT scan was performed to detect BAM. Demographic and treatment data was recorded in the trial documentation. Results: Twenty patients underwent a SeHCAT scan. Ten patients had cervical cancer and 10 had bladder cancer, of which 9 were male. All patients received 20 fractions of radiotherapy over 4 weeks. See table for full demographics. SeHCAT was completed a median 25 days following the start of radiotherapy (28 days for cervix group, 24 days for bladder group). Overall the prevalence of BAM was 65% (13/20). SeHCAT was positive in 90% of the cervix group and 40% of the bladder group. Of the 13 patients who had BAM the prevalence of mild (7-day retention 10–15%), moderate (7-day retention 5–10%) and severe BAM (7-day retention <5%) were 23%, 31% and 46% respectively. There were no patients with 7-day retention of 15–20%. The median 7-day retention of all patients with BAM was 5% while for those without BAM it was 36%. Of the 4 patients who had VMAT (a newer technique), 3 had BAM suggesting that this technique is still strongly associated with small bowel effects. Conclusion: Despite advances in radiotherapy techniques, we found a similar rate of BAM in this group compared to historical data. However the rate of BAM differed between the 2 patient groups suggesting that treatment factors may play a role and that these patient groups may not be homogeneous. Disclosure of interest: K. White Grant/ Research Support from: This poster presents independent research funded by the National Institute for Health Research (NIHR) under its Research for Patient Benefit (RfPB) Programme (Grant Reference Number PB-PG-0211–10024. The views expressed are those of the author (s) and not necessarily those of the NHS, the NIHR or the Department of Health., C. Henson: None Declared, K. Jenner: None Declared, S. Burden: None Declared, S. Lal: None Declared, S. Davidson: None Declared, J. McLaughlin: None Declared.